The Combined Relationship of Vitamin D and Weight-Bearing Sports Participation on Areal Bone Density and Geometry Among Adolescents: ABCD - Growth Study - Mesquita, Eduardo Duarte de Lima [UNESP]; Exupério, Isabella Neto [UNESP]; Agostinete, Ricardo Ribeiro [UNESP]; Luiz-de-Marco, Rafael [UNESP]; da Silva, Jéssica Casarotti Miguel [UNESP]; Maillane-Vanegas, Santiago [UNESP]; Kemper, Han C G; Fernandes, Rômulo Araújo [UNESP] (Elsevier, 2022)
Osteoporosis is a public health problem, which negatively impacts society and national health services worldwide. Altered mineralization of the skeleton can be caused by persistent vitamin D deficiency. However, the combined impact of both on bone health is still under investigation. In fact, although there is compelling evidence in the literature about the positive effect of weight-bearing sports participation on bone mineral density, its impact on bone geometry gains more attention in pediatric population. The sports modalities that we evaluated were artistic gymnastics and track and field. Nonsports group was composed of 43 adolescents. Bone density was assessed using dual-energy X-ray absorptiometry. Vitamin D concentration was assessed by blood analysis. In the crude comparison of bone outcomes, the sport group presented higher aBMD only in the trochanter (p-value = 0.040). Considering the combination of the engagement in sports and vitamin D, adolescents in the sports group presented significantly higher values of aBMD in lower limbs, whole body, trochanter, shaft, and femur whole body (p-value = 0.024, 0.035, 0.001, 0.019 and 0.003 respectly). In contrast, only the sport group with high vitamin D presented a higher CSA (p-value = 0.015) and femur neck aBMD compared to the non-sport/low vitamin D group. Only adolescents with a combination of sports participation and higher serum concentrations of vitamin D presented better bone geometry, denoting the relevance of the combination of both factors to bone health.
Keywords: Adolescents; Bone; Vitamin D; Weight-bearing sports